Determinants of Compliance of Pregnant Women in Participating in the Class Program for Pregnant Women in Aceh Besar District - Alfiana, Alfiana; Z, Nasrul; Usman, Said; Maulana, T.; Saputra, Irwan (Journal of World Science, 2023)
The implementation of the pregnant women class in Aceh Besar Regency has been carried out since 2020 with a target of 11,492 pregnant women. From observations, it is known that most pregnant women are less obedient in attending maternity classes. So, the purpose of this study is to analyze the compliance of pregnant women in participating in the class program for pregnant women in Aceh Besar district. This type of research uses observational cross-sectional design. The population of this study included classes of pregnant women at Indrapuri Health Center, Kuta Baro Health Center, and Darul Imarah Health Center, the sample in this study amounted to 180 pregnant women. The study found that the R-square value for service satisfaction was 0.694 and that internal and external factors could affect the compliance variables of pregnant women by 69.4%, with the remaining 30.6% influenced by other factors. Additionally, the implementation of the pregnant women class program was found to have an R-square value of 0.667, indicating that internal and external factors could affect it by 66.7%, with the remaining 33.3% influenced by other factors. The study also identified external factors, specifically knowledge, as the primary influencing factor on the implementation of the pregnant women class program, with a calculated value of 35,768 > table 1,624. Internal factors (age, income, motivation, and parity) and external factors (knowledge, attitudes, family support, and mileage) influence the compliance of pregnant women and the implementation of classes for pregnant women in Aceh Besar District.